IMPLEMENTASI RODA GIGI CACING PADA ALAT PEMBENTUK MOTIF PADA KERAJINAN PLAT SENG - A. A. A. Suryawan; N. Suweden; I N. G. Antara; I G. N. O. Suputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
Craft industry center of trinkets ornaments made from zinc plates and other simillar materials in Baliprovince is developing quite rapidly. As household handicraft business, this business has been progressingtypes and forms in many variations. In the development of this business is experiencing problems such asdecreased selling prices of production due to competition among craftsmen, high labor costs, and a lack oftechnical capacity and production innovation. For that needed guidance and help to increase productioncapacity and diminishes the cost of production. One of them by applying a usefull technology in themanufacture of the motif on the zinc plate. Making pattern requires the longest time in the production process,therefore it is necessary introduced a usefull technology that is a impact tool by implementing worm gear tocreate a motif in accordance with the desired shape. So, it would facilitate and accelerate the process,including by mothers who have aged. Based on the prototype that has been designed and constructed, theresulting pattern forming tool has been able to function properly. Although at the beginning of the operationby craftsperson are still slow, but with more frequent operate it they will be familiar, and pattern making willbe faster and is expected to reduce the noise that occurs. IMPLEMENTASI RODA GIGI CACING PADA ALAT PEMBENTUK MOTIF PADA KERAJINAN PLAT SENG